Pengaruh Pengembangan Wisata Bendungan Way Sekampung Terhadap Pendapatan Ekonomi Masyarakat Pekon Bumi Ratu - Dita Rani Setya Ningrum; Yenny Marthalena (Journal on Education, 2025)
This research aims to determine the influence of the Way Sekampung Dam tourism development on the economic income of the Pekon Bumi Ratu community. This research uses quantitative methods. The sampling technique used purposive sampling, where the population in this study was the entire community in Pekon Bumi Ratu, totaling 3093 respondents, with a sample of 100 respondents. Primary data in this research was obtained directly from respondents. Data collected using observation, questionnaires and documentation. The data analysis method used is simple linear regression analysis. The results of the research show that the Tourism Development of the Way Sekampung Dam (X) has a significant effect on the Economic Income of the Pekon Bumi Ratu community with a calculated t value of 3.350 > t table value of 1.984.